Food allergy testing in atopic dermatitisCapsule Summary - Hassiel A. Ramírez-Marín, MD; Anne Marie Singh, MD; Peck Y. Ong, MD; Jonathan I. Silverberg, MD, PhD, MPH (Elsevier, 2022)
Food allergy and food-related worsening of dermatitis can occur in patients with atopic dermatitis (AD). We reviewed the relationship of AD with food allergen hypersensitivity and the risks and benefits of food allergen testing and avoidance in patients with AD. Skin prick testing and specific immunoglobulin E to aeroallergens may identify patients with immediate hypersensitivity. Atopy patch tests may detect non-immunoglobulin E-mediated reactions but are not standardized or routinely used. Younger children with more severe AD in whom the optimal management failed may have food-triggered AD. Egg, milk, and peanut account for most food allergens. Elimination of relevant food allergens should improve AD but must be guided by appropriate allergy testing and establishing clinical relevance. Serum immunoglobulin E panels for food allergens are discouraged in the primary care setting because of their difficulty of interpretation. Empiric avoidance of foods is entirely discouraged in AD because of their risk of causing nutritional issues, food allergy, and other problems.